Micromégas: Altered Body–Environment Scaling in Literary Fiction - Dieguez, Sebastian (Frontiers in Psychology, 2016)
Architectonic embodiment postulates a bidirectional link between bodily awareness and the architectural environment. The standard size and features of the human body, for instance, are thought to influence the structure of interiors and buildings, as well as their perception and appreciation. Whereas architectural practice and theory, the visual arts and more recently the cognitive sciences have explored this relationship of humans with their crafted environments, many fictional literary works have long experimented with alterations of body-environment scaling. This so-called “Gulliver theme” - popular in the science-fiction genre but also in children’s literature and philosophical satire – reveals, as a recurrent thought-experiment, our preoccupation with proportions and our fascination for the infinitely small and large. Here I provide an overview of the altered scaling theme in literature, including classics such as Voltaire’s Micromégas, Swift’s Gulliver’s Travels, Caroll’s Alice and Matheson’s The Shrinking man, closely examining issues relevant to architectonic embodiment such as: bodily, perceptual, cognitive, affective, and social changes related to alterations in body size relative to people, objects and architectural environments. I next provide a taxonomy of the Gulliver theme and highlight its main psychological features, and then proceed to review relevant work from cognitive science. Although fictional alterations of body-environment scaling far outreach current possibilities in experimental research, I argue that the peripetiae and morals outlined in the literary realm, as products of the human imagination, provide a unique window into the folk-psychology of body and space.